Leukocyte Glucose Index as Significant Marker of Poor Prognosis in COVID-19 Patients with Hyperglycemia - Al-Nimer, Marwan; Merza, Talar A.; Jawad, Thaqeef M.; Latif, Ismail I. (Bangladesh Journal of Infectious Diseases, 2025)
Background: Both diabetes mellitus (DM) and stress hyperglycemia (SH) are common findings in complicated or critically ill COVID-19 patients. Objective: This retrospective study aims to assess leukocyte glucose index (LGI) as a prognostic marker for the outcome of COVID-19 patients. Methodology: This retrospective study was conducted at the College of Medicine, University of Diyala, Iraq. Patients with COVID-19 were randomly allocated. A primary outcome of this study was clinical outcomes in terms of surviving or not surviving. Results: 187 patients in total were included in the study and divided into three groups. Group I (n = 45) survived patients, Group II (n = 90) survived patients with complications, and Group III (n = 52) non-survived patients. The baseline data showed significant differences between Groups III, I, and II. The median values of LGI were significantly (p <0.001) higher in Group III (2.911) compared with Group I (1.754) and Group II (1.728). The odds ratio of DM, SH, and LGI (a cutoff value of 1.5) as a risk of mortality is 2.361, 7.333, and 4.842, respectively. Conclusion: Leukocyte glucose index is a worse marker for COVID-19 patients with overt diabetes or stress hyperglycemia. Bangladesh Journal of Infectious Diseases, December 2024;11(2):102-107